Furrow opener and plant density on canola crop, penetration resistance and subsequent soybean crop (Research, Society and Development, 2020)
Canola (Brassica napus L.) presents itself economically and agronomically interesting as a winter crop for southern brazilian producers. There is questioning about the seeding technology for this crop. Thus, the objective of this work was to evaluate the furrowing mechanism (of the fertilizer distribution system) and plant population in the canola crop, and its effects on soil penetration resistance and subsequent soybean crop. Two plant densities of canola (20 and 40 plants m2) and two furrow openers (furrowing shank and double disc) were used with six repetitions in random blocks. It was sown with a pneumatic precision seeding machine with 50 cm spacing between lines. In canola, the variables evaluated were: Plant number per meter (PN), Thousand seeds mass (TSM), Grain Yield (GY), Root length (RL), Root volume (RV), Shoot dry matter (SDM), Root dry matter (RDM) and penetration resistance (PR). In soybean, yield, thousand seeds weight and stem diameter (SD) were quantified. The density of 40 plants m-2 provides greater yield, regardless of the furrowing mechanism. There is less PR in the sowing line when using a furrowing shank, after the canola seeding. The furrowing shank promoted higher RL, and lower SDM and RDM. Canola management, in terms of population and furrow mechanism, did not affect the soybean cultivated in the sequence.